2020
DOI: 10.1108/jic-12-2019-0302
|View full text |Cite
|
Sign up to set email alerts
|

The link between intellectual capital and business performance: a mediation chain approach

Abstract: PurposeThis study focuses on intellectual capital (IC) as a driver of better business performance. Recent studies suggest that a set of variables may mediate this relationship. This research discusses the mediating role of dynamic capabilities, network competence, technological capabilities, absorptive capabilities and innovation performance between intellectual capital and business performance.Design/methodology/approachThe conceptual model is tested using a sample of 533 Portuguese firms by means of a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 77 publications
6
53
0
3
Order By: Relevance
“…Financial performance includes accounting operations and financial measures. Operational performance is related to efficiency, namely, technological capabilities in managing company products and human assets (Campos et al , 2022). The company will continue to try to improve performance by focusing on cost reduction and efficiency, as well as comply with regulations taking into account the stakeholders of good practice, and jointly lead to stakeholders and consumer attractiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial performance includes accounting operations and financial measures. Operational performance is related to efficiency, namely, technological capabilities in managing company products and human assets (Campos et al , 2022). The company will continue to try to improve performance by focusing on cost reduction and efficiency, as well as comply with regulations taking into account the stakeholders of good practice, and jointly lead to stakeholders and consumer attractiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, to overcome the risks of failure, startups need to develop the ability to create, organize and direct the set of their knowledge to promote innovation in the organizational context (Cassol et al, 2016;Iencieu and Matis, 2011), developing important assets related to its intellectual capital to increase its competitiveness and sustainability, especially in the current times of the knowledge economy (Campos et al, 2020;Cassol et al, 2016;Iencieu and Matis, 2011;Nahapiet and Ghoshal, 1998;Petty and Guthrie, 2000).…”
Section: Life Cycle Analysis Ofmentioning
confidence: 99%
“…In an increasingly dynamic and competitive context, studies have shown that a company's ability to create, organize and direct the sum of its knowledge related to the human, structural and relational fields can be a fundamental strategy for its survival and sustainability, by promoting innovation in the organizational context (Cassol et al, 2016;Iencieu and Matis, 2011). Since then, understood as the sum of all knowledge held in a company (Stewart, 1998), the concept of intellectual capital has developed and reflected the importance that understanding the knowledge factor has acquired within organizations and its role in the evolution of (Campos et al, 2020;Nahapiet and Ghoshal, 1998), providing the organization with a competitive advantage (Stewart, 1998).…”
Section: Intellectual Capitalmentioning
confidence: 99%
See 2 more Smart Citations